Availability of Internationally Controlled Essential Medicines in the COVID-19 Pandemic - Pettus, Katherine (J Pain Symptom Manage, 2020)
Section 2 of the 2019 World Health Organization Model List of Essential Medicines includes opioid analgesics formulations commonly used for the control of pain and respiratory distress, as well as sedative and anxiolytic substances such as midazolam and diazepam. These medicines, essential to palliative care, are regulated under the international drug control conventions overseen by United Nations specialized agencies and treaty bodies and under national drug control laws. Those national laws and regulations directly affect bedside availability of Internationally Controlled Essential Medicines (ICEMs). The complex interaction between national regulatory systems and global supply chains (now impacted by COVID-19 pandemic) directly affects bedside availability of ICEMs and patient care. Despite decades of global civil society advocacy in the United Nations system, ICEMs have remained chronically unavailable, inaccessible, and unaffordable in low- and-middle-income countries, and there are recent reports of shortages in high-income countries as well. The most prevalent symptoms in COVID-19 are breathlessness, cough, drowsiness, anxiety, agitation, and delirium. Frequently used medicines include opioids such as morphine or fentanyl and midazolam, all of them listed as ICEMs. This paper describes the issues related to the lack of availability and limited access to ICEMs during the COVID-19 pandemic in both intensive and palliative care patients in countries of all income levels and makes recommendations for improving access.